Understanding the interactions between sebum triglycerides and water: a molecular dynamics simulation study. - Tascini,AS; Noro,MG; Chen,R; Seddon,JM; Bresme,F (Physical Chemistry Chemical Physics, 2018)
In recent years, sebum oil has been found to play a key role in the regulation of the hydration of the outermost layer of the skin, the stratum corneum. Understanding how a major component of the sebum oil, the triglyceride tri-cis-6-hexadecenoin (TG), interacts with water is an important step in gaining insight into the water regulation function of the sebum oil. Here we use molecular dynamics simulations to investigate the structural and interfacial properties of TG in bulk and at the air and water interface. Our model performs very well in reproducing experimental results, such as density, surface tensions and surface pressure area isotherms. We show that triglyceride molecules in the liquid phase assemble together, through the glycerol group, forming a single percolating network. TG-air interfaces orient the lipids with the interface enriched with the hydrophobic tails and the glycerol groups buried inside. When in contact with water, the TG molecules at the interface orient the glycerol group towards the water phase and adopt a characteristic trident conformation. Water is shown to penetrate the TG layer thanks to the interaction with the oxygen atoms of the TG molecules, which acts as a pathway for water diffusion. The activation energy for the passage of water is found to be ≈9.5kBT at 310 K, showing that the layer is permeable to water diffusion.